2016
DOI: 10.3839/jabc.2016.035
|View full text |Cite
|
Sign up to set email alerts
|

Control effects of LED trap toSitotroga cerealellaandPlodia interpunctellain the granary

Abstract: This study was conducted to evaluate the attraction effects of Sitotroga cerealella and Plodia interpunctella adults to light emitting diode (LED) trap in granary and compared with the results of the black light bulb (BLB) trap, which is typically used as a commercial trap. The blue LED was more attractive to S. cerealella than the BLB. The green LED was significantly more attractive to P. interpunctella than the BLB. Furthermore, the external installation of blue LED and green LED was about 1.7 times more att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…Similar to our study, found repellent effect of the blue light to Lasioderma serricorne (Fabricius, 1792) (Coleoptera: Anobiidae). In contrast to our study, Jeon & Lee (2016) reported that blue light is the most attractive to Sitotroga cerealella (Olivier, 1789) (Lepidoptera: Gelechiidae). Also, in contrast to our study, Jeon et al (2012) reported blue light attraction in Sitophilus oryzae (Linnaeus, 1763) (Coleoptera: Curculionidae).…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to our study, found repellent effect of the blue light to Lasioderma serricorne (Fabricius, 1792) (Coleoptera: Anobiidae). In contrast to our study, Jeon & Lee (2016) reported that blue light is the most attractive to Sitotroga cerealella (Olivier, 1789) (Lepidoptera: Gelechiidae). Also, in contrast to our study, Jeon et al (2012) reported blue light attraction in Sitophilus oryzae (Linnaeus, 1763) (Coleoptera: Curculionidae).…”
Section: Discussioncontrasting
confidence: 99%
“…violet and ultraviolet) attracted the beetles. Jeon et al (2016) evaluated the attraction effects of Sitotroga cerealella and Plodia interpunctella adults to LED traps in granary and found that the green LED was significantly more attractive to P. interpunctella than the BLB. Duehl et al (2011) compared the responses to light spectra across the visible and UV regions of the electromagnetic spectrum which indicated that Tribolium castaneum was most attracted to near UV LED at a 390 nm dominant wavelength.…”
Section: Resultsmentioning
confidence: 99%